Spurred nodular precursor, cathode material, and method for manufacturing the same

JP7936846B2Active Publication Date: 2026-10-16南方もん業集団有限責任公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024130491
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-03-26
Filing Date
2024-08-07
Publication Date
2026-10-16
Estimated Expiration
2044-08-07

Smart Images

  • Figure 0007936846000002
    Figure 0007936846000002
  • Figure 0007936846000003
    Figure 0007936846000003
  • Figure 0007936846000004
    Figure 0007936846000004
Patent Text Reader

Abstract

To provide a dense thorn cluster-shaped precursor, a positive electrode material and a preparation method of the dense thorn cluster-shaped precursor and the positive electrode material.SOLUTION: A dense thorn cluster-shaped precursor is a porous particle formed by aggregating fine needle-shaped primary particles. The dense thorn cluster-shaped precursor is prepared from a mixture comprising a ternary solution, a precipitator solution, a complexing agent solution and a treatment solution. The ternary solution is a mixed solution comprising nickel salt, cobalt salt and manganese salt. The treating fluid is a citric acid solution. The dense thorn cluster-shaped precursor provided by the invention is a porous particle formed by aggregating fine needle-shaped primary particles, the lithium ion transport rate can be improved, the fine needle-shaped primary particles have a relatively large specific surface area and can provide more active sites, and the positive electrode material with good surface structure stability can be obtained after the fine needle-shaped primary particles and a lithium source are mixed and sintered at a high temperature.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to the technical field of lithium-ion battery cathode materials, and more particularly to a punctured nodular precursor, a cathode material, and a method for producing the same. [Background technology]

[0002] Developing electric vehicles is a crucial strategic choice in our country to meet the demands of the national energy strategy and achieve the carbon neutrality target of 2060. Lithium-ion batteries have been widely developed due to their advantages over other batteries such as nickel-metal hydride batteries and lead-acid batteries, including light weight, low self-discharge rate, high energy density, and long cycle life. However, the capacity of lithium-ion batteries is limited by the performance of the cathode material, and one-third of the battery cost is spent on research to improve the performance of the cathode material. Currently, the cathode materials used in lithium-ion batteries are mainly lithium cobalt oxide, lithium iron phosphate, and ternary materials. Of these, ternary materials are widely studied because they have advantages such as high specific capacity, good cycle characteristics and C-rate characteristics, and low cost, but they face many challenges.

[0003] Current ternary cathode materials mainly suffer from problems such as cation mixing, lattice oxygen deposition, transition metal ion migration, and microcrack formation, which lead to structural breakdown, generation of inert substances, rapid capacity decay, and invalidation of the final material, hindering the commercial use of ternary cathode materials. Patent document CN111153447A describes how to produce a mesh-like porous precursor material by adding solutions of nickel, cobalt, manganese, etc., complexing agents, precipitating agents, and pore-forming agents together in parallel flow to a reactor having a predetermined bottom liquid in a predetermined gas atmosphere, and continuously carrying out a coprecipitation reaction. The primary particles have a planar arrangement, a vertical arrangement, or a mixed arrangement of both, and the secondary particles have good dispersibility and high sphericity. Patent document CN112758991A describes how to increase structural strength by forming a mesh structure on the outer layer of precursor particles using a polymer flocculant, thereby avoiding spherical breakage due to collisions between particles in the later stages of the precursor reaction and ensuring circulation, stability, and safety. However, the above method had problems such as uneven particle size, poor uniformity of properties, insufficient grain growth, and primary particles falling off in subsequent cycles. [Overview of the Initiative]

[0004] The present invention provides a spiky nodular precursor, a cathode material, and a method for producing the same, addressing one or more technical problems in the prior art. The spiky nodular precursor of the present invention is a porous particle formed by the aggregation of fine needle-shaped primary particles, having a uniform particle size distribution and high sphericity. Within it, the fine needle-shaped primary particles are distributed longitudinally and transversely, forming a certain pore structure that accelerates lithium ion transport rate. Furthermore, the good spherical structure provides a basis for improving subsequent cycle performance. The fine needle-shaped primary particles have a relatively large specific surface area, which can provide more active sites. After mixing with a lithium source and firing at high temperature, a cathode material with good surface structure stability can be obtained.

[0005] In a first embodiment, the present invention provides a porous particle formed by the aggregation of fine needle-shaped primary particles, The aforementioned punctate nodular precursor is prepared from a mixture comprising a ternary solution, a precipitant solution, a complexing agent solution, and a treatment solution; The ternary solution is a mixed solution containing a nickel salt, a cobalt salt, and a manganese salt, and the treatment solution provides a citric acid solution that provides a nodular precursor of punctate cells.

[0006] Preferably, the nickel salt, cobalt salt, and manganese salt are independently one or more selected from sulfates, nitrates, and carbonates; and / or The precipitating agent solution is a carbonate solution, preferably one or more selected from sodium carbonate solution, sodium bicarbonate solution, potassium carbonate solution, potassium bicarbonate solution, and rubidium carbonate solution, and more preferably the concentration of the sodium carbonate solution is 0.2 to 4.5 mol / L.

[0007] Preferably, the concentration of metal ions in the ternary solution is 0.6 to 2.5 mol / L; The precipitating agent solution is a solution containing carbonate ions, and preferably the carbonate ion concentration in the precipitating agent solution is 0.8 to 3.4 mol / L; The complexing agent solution is aqueous ammonia, preferably with a concentration of 4-7 mol / L; and / or The concentration of the citric acid is 0.025 to 0.1 mol / L.

[0008] In a second embodiment, the present invention provides a method for producing a spiky nodular precursor according to the first embodiment, comprising the following steps: S1. Prepare the ternary solution, precipitant solution, complexing agent solution, and treatment solution separately; S2. Under a protective atmosphere, the complexing agent solution and the precipitating agent solution are mixed to prepare the primer solution; S3. Mix the ternary solution, the treatment solution, and the primer solution, and after the first reaction, allow to stand, remove the supernatant, and produce the first product; S4. The first product is mixed with the ternary solution, the precipitating agent solution, and the complexing agent solution, the second reaction is carried out, the mixture is allowed to stand, and the supernatant is removed; S5. A method for producing a spiky, nodular precursor is provided, which involves repeating step S4 at least once, followed by maturation, washing, drying, sieving, and iron removal.

[0009] Preferably, the primer solution has a pH of 11 to 12; and / or The ammonia concentration of the primer solution is 2 to 20 g / L.

[0010] Preferably, the temperatures of the first and second reactions are independently 30-60°C; The durations of the first and second reactions were independently 0.5 to 5 hours; The first and second reactions have a pH of 7.5 to 8.5 independently; and / or The aforementioned maturation time is 5 to 20 hours.

[0011] In a third embodiment, the present invention provides a cathode material obtained by kneading a spiky nodular precursor described in the first embodiment with a lithium source and then heat-treating it.

[0012] Preferably, the ratio of the spiky nodular precursor to the lithium source is 1:1.03 to 1.10; and / or The lithium source is one or more selected from lithium hydroxide, lithium nitrate, and lithium carbonate.

[0013] Preferably, the chemical formula of the positive electrode material is LiNi x Co y Mn (1-x-y) O2( 0.6≦x<1, 0 <y≦0.4 )である。

[0014] Preferably, the mixing is ball mill mixing, the ball mill having a rotational speed of 1800-2000 r / min and a time of 2-4 hours; and / or Said heat treatment is carried out by holding the temperature at 480~850°C for 12~18 hours in an oxygen atmosphere; preferably, in said heat treatment, the airflow rate of oxygen gas is 80~120 mL / min; preferably, the heat treatment is performed by holding the temperature at 480~550°C for 4~6 hours, then holding the temperature at 700~850°C for 9~12 hours, with a temperature rise rate of 2~5°C / min.

[0015] The present invention exhibits at least the following advantageous effects compared with the prior art.

[0016] The present invention provides a spiky nodular precursor with uniform particle size distribution and high sphericity. Said spiky nodular precursor is a porous particle formed by agglomeration of fine acicular primary particles, which has uniform particle size distribution and high sphericity. Among them, the fine acicular primary particles are distributed vertically and horizontally to form a definite pore structure, which accelerates the lithium ion transport rate, and the favorable spherical structure provides a basis for the subsequent improvement of cycle performance. The fine acicular primary particles have a relatively large specific surface area, which can provide more active sites, and can obtain a cathode material with good surface structure stability after being mixed with a lithium source and calcined at high temperature.

[0017] According to the present invention, a treatment liquid is introduced into a coprecipitation system of a ternary solution, a precipitant solution and a complexing agent, the parameters of the precursor synthesis conditions are adjusted to make crystal grains grow anisotropically, so as to produce a porous spiky nodular precursor formed by agglomeration of fine acicular primary particles. The pores serve as lithium ion transport channels, which is beneficial to improving the cycle performance of the cathode material, and at the same time, reduces the surface alkali content, avoids the destruction of the material surface structure and the loss of raw materials caused by long-time water washing using a large amount of water, and can further improve the electrochemical performance such as the cycle performance of the cathode material. Furthermore, after being mixed with the lithium source and subjected to heat treatment, the fine acicular primary particles can be further grown to be striated and intertwined with each other, so as to improve the stability of the surface structure and further enhance the C-rate characteristics. Brief Description of the Drawings

[0018] To make the technical aspects in the examples of the present invention or the prior art clearer, the drawings required in the description of the examples or the prior art are briefly described below. The drawings in the following description form part of the examples of the present invention, and it is obvious for those skilled in the art that other drawings can be derived based on these drawings without creative work. [Figure 1] Figure 1 is an SEM photograph of the acicular agglomerated precursors provided in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; [Figure 2] Figure 2 is an SEM photograph of the secondary particles after heat treatment in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; [Figure 3] Figure 3 shows the initial charge-discharge curves of the positive electrode materials prepared in Example 1 and Comparative Example 1 of the present invention at a current density of 18 mA / g; [Figure 4] Figure 4 shows the initial charge-discharge curves of the positive electrode materials prepared in Example 1, Example 2 and Comparative Example 1 of the present invention at a current density of 180 mA / g; [Figure 5] Figure 5 shows the cycle characteristics at different C rates of the positive electrode materials prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention. Mode for Carrying Out the Invention

[0019] To make the objectives, technical solutions and advantages of the examples of the present invention clearer, the present invention is clearly and completely described below with reference to the technical solutions in the examples of the present invention. In addition, the examples described below are part of the examples of the present invention, not all of the examples. All other embodiments obtained by a person of ordinary skill in the art based on the examples of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0020] In a first aspect, the present invention relates to a porous particle formed by agglomeration of fine acicular primary particles, The acicular agglomerated precursor is prepared from a mixture comprising a ternary solution, a precipitant solution, a complexing agent solution, and a treatment solution; The ternary solution is a mixed solution containing a nickel salt, a cobalt salt, and a manganese salt, and the treatment solution provides a citric acid solution that provides a nodular precursor of punctate cells.

[0021] The punctured nodular precursor of the present invention is a porous particle formed by the aggregation of fine needle-shaped primary particles, having a uniform particle size distribution and high sphericity. Within it, the fine needle-shaped primary particles are distributed longitudinally and transversely, forming a certain pore structure that accelerates lithium ion transport rate. Furthermore, the good spherical structure provides a basis for improving subsequent cycle performance. In addition, the fine needle-shaped primary particles have a relatively large specific surface area, which can provide more active sites, and after mixing with a lithium source and firing at high temperature, a cathode material with good surface structure stability can be obtained.

[0022] In some preferred embodiments, the nickel salt, cobalt salt, and manganese salt are independently one or more selected from sulfates, nitrates, and carbonates.

[0023] In some preferred embodiments, the precipitating agent solution is a carbonate solution, preferably one or more selected from sodium carbonate solution, sodium bicarbonate solution, potassium carbonate solution, potassium bicarbonate solution, and rubidium carbonate solution, and more preferably the concentration of the sodium carbonate solution is 0.2 to 4.5 mol / L, for example, 0.2 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, or 4.5 mol / L.

[0024] In some preferred embodiments, the concentration of metal ions in the ternary solution is 0.6 to 2.5 mol / L, for example, 0.6 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 2 mol / L, or 2.5 mol / L.

[0025] In some preferred embodiments, the precipitating solution is a solution containing carbonate ions, and preferably the carbonate ion concentration in the precipitating solution is 0.8 to 3.4 mol / L, for example, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, 2.5 mol / L, 3 mol / L, 3.2 mol / L, or 3.4 mol / L.

[0026] In some preferred embodiments, the complexing agent solution is aqueous ammonia, preferably with a concentration of 4 to 7 mol / L, for example, 4 mol / L, 4.5 mol / L, 5 mol / L, 5.5 mol / L, 6 mol / L, 6.5 mol / L, or 7 mol / L.

[0027] In some preferred embodiments, the concentration of the citric acid is 0.025 to 0.1 mol / L, for example, 0.025 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, or 1 mol / L.

[0028] In a second embodiment, the present invention provides a method for producing a spiky nodular precursor according to the first embodiment, comprising the following steps: S1. Prepare the ternary solution, precipitant solution, complexing agent solution, and treatment solution separately; S2. Under a protective atmosphere, the complexing agent solution and the precipitating agent solution are mixed to prepare the primer solution; S3. Mix the ternary solution, the treatment solution, and the primer solution, and after the first reaction, allow to stand, remove the supernatant, and produce the first product; S4. The first product is mixed with the ternary solution, the precipitating agent solution, and the complexing agent solution, the second reaction is carried out, the mixture is allowed to stand, and the supernatant is removed; S5. The present invention provides a manufacturing method for producing a nodular precursor of spiky material by repeating step S4 at least once, followed by maturation, washing, drying, sieving, and iron removal.

[0029] This invention involves introducing a processing solution into a coprecipitation system of a ternary solution, a precipitant solution, and a complexing agent, adjusting the parameters of the precursor synthesis conditions, and producing a porous, spiky nodular precursor formed by the aggregation of fine needle-shaped primary particles. The pores serve as lithium ion transport passages, which is advantageous for improving the cycle performance of the cathode material. At the same time, it reduces the surface alkali content, avoids the destruction of the material surface structure and loss of raw materials due to prolonged washing with large amounts of water, and can further improve the electrochemical performance, such as the cycle performance, of the cathode material. Furthermore, when mixed with a lithium source and heat-treated, the fine needle-shaped primary particles are further grown, becoming streaky and intertwined with each other, improving the stability of the surface structure and further improving the C-rate characteristics.

[0030] This invention employs a coprecipitation method to prepare fine needle-shaped precursors, and further prepares a high-nickel ternary cathode material. Through research and optimization, several sets of manufacturing condition parameters were derived, expanding the conditions for the practical production and application of high-nickel cathode materials. The method of this invention is economically feasible, widely applicable, effective, and has promising application prospects.

[0031] In some preferred embodiments, the primer solution has a pH of 11 to 12, for example, 11, 11.2, 11.4, 11.6, 11.8, or 12. In the present invention, by controlling the pH of the primer solution within the above range, nucleation can be rapidly performed when the ternary solution is injected, thereby promoting granulation.

[0032] In some preferred embodiments of the present invention, in S2, under a nitrogen atmosphere, a complexing agent solution is added to pure water, and the pH is adjusted with a precipitating agent solution to prepare the primer solution. The stirring speed during mixing is 400 to 600 rpm.

[0033] In some preferred embodiments, the primer solution has an ammonia concentration of 2 to 20 g / L, for example, 2 g / L, 5 g / L, 6 g / L, 8 g / L, 10 g / L, 12 g / L, 15 g / L, 16 g / L, 18 g / L, or 20 g / L.

[0034] In some preferred embodiments, the temperatures of the first and second reactions are independently 30 to 60°C, for example, 30°C, 40°C, 50°C, or 60°C.

[0035] In some preferred embodiments, the duration of the first reaction and the second reaction are independently 0.5 to 5 hours, for example, 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, or 5 hours.

[0036] In some preferred embodiments, the pH of the first and second reactions is independently 7.5 to 8.5.

[0037] In some preferred embodiments, the maturation time is 5 to 20 hours, for example, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, or 20 hours.

[0038] In some preferred embodiments of the present invention, in S3 and S4, the stirring speeds of the first reaction and the second reaction are independently 300 to 1200 rpm.

[0039] In some specific embodiments of the present invention, after the first reaction, the reaction solution is allowed to stand for 0.1 to 10 hours, the supernatant is removed, then the ternary solution, precipitant solution and complexing agent solution are injected by pump to carry out the second reaction, and the process of letting it stand and removing the supernatant is repeated 1 to 10 times (the process of injecting the ternary solution, precipitant solution and complexing agent solution by pump, carrying out the second reaction, letting it stand and removing the supernatant), and after maturation for 5 to 20 hours, the slurry is washed 2 to 15 times with deionized water; the matured slurry is placed in deionized water and allowed to stand for 0.2 to 3 hours, and the supernatant is removed to remove impurity ions, and the washing is carried out in this manner.

[0040] In this invention, in order to ensure uniformity of the particle size of the precursor, step S4 is repeated 1 to 10 times.

[0041] In a third embodiment, the present invention provides a cathode material obtained by kneading a spiky nodular precursor described in the first embodiment with a lithium source and then heat-treating it.

[0042] In some preferred embodiments, the ratio of the punctate nodular precursor to the lithium source is 1:1.03 to 1.10, for example 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09 or 1:1.1, and / or The lithium source is one or more selected from lithium hydroxide, lithium nitrate, and lithium carbonate.

[0043] In some preferred embodiments, the chemical formula of the positive electrode material is LiNi x Co y Mn (1-x-y) O2( 0.6≦x<1, 0 <y≦0.4 )である。

[0044] In some preferred embodiments, the kneading is ball mill mixing, the ball mill having a rotational speed of 1800 to 2000 r / min, for example 1800 r / min, 1900 r / min or 2000 r / min, a duration of 2 to 4 hours, for example 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours, and / or In some preferred embodiments, the heat treatment is carried out in an oxygen atmosphere at 480-850°C (e.g., 480°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, or 850°C) for 12-18 hours (e.g., 12, 13, 14, 15, 16, 17, or 18 hours); preferably, the oxygen gas flow rate in the heat treatment is 80-120 mL / min (e.g., 80 mL / min, 90 mL / min, 100 mL / min, 110 mL / min, or 120 mL / min); if the oxygen gas flow rate of the present invention is lower than this range, it will lead to oxygen deficiency, which is unfavorable for oxide formation. Also, if the flow rate is too high, the actual temperature will be insufficient, and the desired temperature effect will not be obtained.

[0045] In some preferred embodiments, the heat treatment is performed by first heating to 480-550°C (e.g., 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, or 550°C) for 4-6 hours (e.g., 4 hours, 4.5 hours, 4 hours, 4.5 hours, or 6 hours), then heating to 700-850°C (e.g., 700°C, 750°C, 800°C, or 850°C) for 9-12 hours (e.g., 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours, or 12 hours), with a heating rate of 2-5°C / min (e.g., 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, or 5°C / min). In this invention, if the heating rate is too low, the time cost increases, as does the cost of electricity and oxygen. On the other hand, if the heating rate is too high, the particles expand and collapse at high temperatures. Therefore, the heating rate of the heat treatment is controlled within the above range.

[0046] To more clearly illustrate the technical modes and advantages of the present invention, the present invention will be further described below with reference to examples.

[0047] Example 1 Method for producing nodular precursors of punctate fungi: S1. Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 83:11:6, and pure water was added and stirred to dissolve, preparing a ternary solution with a total metal ion concentration of 1.5 mol / L. A 2 mol / L aqueous solution of sodium carbonate was prepared as a precipitating agent solution. A complexing agent solution was prepared with a concentration ratio of 2.5 between aqueous ammonia and sodium carbonate. A citric acid solution was prepared as a treatment solution, and the concentration ratio of the citric acid solution to sodium carbonate was 0.0125.

[0048] S2. Nitrogen gas was injected using an air pump, and the complexing agent solution was added to pure water under a nitrogen atmosphere. The primer solution was then controlled to pH 11 with a precipitating agent solution, with an ammonia concentration of 8 g / L, a temperature of 50°C, and a stirring speed of 500 rpm.

[0049] S3. Under a nitrogen atmosphere, the prepared ternary solution and treatment solution were injected into the primer solution and reacted. The stirring speed of the reaction process was adjusted to 800 rpm, the temperature to 60°C, and the pH to 7.5. After feeding for 1 hour, the air pump was closed, the reaction solution was allowed to stand for 2 hours, and then the supernatant was removed. The pump was opened again, and the ternary solution, precipitant solution, and complexing agent solution were continuously injected by the pump and reacted, allowed to stand, and the supernatant was removed. This process was repeated 5 times. After the reaction was complete, the mixture was aged for 12 hours, the aged slurry was washed with deionized water, allowed to stand for 1 hour, the supernatant was removed, and this was repeated 8 times to remove impurity ions. The mixture was dried in a vacuum chamber at 80°C for 15 hours, and the resulting powder was passed through a 200-mesh sieve to remove iron, after which a spiky nodular precursor was obtained.

[0050] Method for manufacturing positive electrode material: 3 g of the obtained spiky nodular precursor and 1.526 g of lithium hydroxide (molar ratio of spiky nodular precursor to lithium hydroxide: 1:1.07) were ball-milled at a rotation speed of 1800 r / min for 3 hours and thoroughly mixed. The mixed material was placed in a tubular furnace and heat-treated with oxygen gas at a flow rate of 80 mL / min. The heat treatment involved first raising the temperature from room temperature to 480°C and holding the temperature for 4 hours, then raising the temperature to 750°C and holding the temperature for 12 hours, after which the furnace temperature was lowered to room temperature, with a heating rate of 3°C / min during the heat treatment process. The obtained material was removed and passed through a 200-mesh sieve to obtain the cathode material.

[0051] Example 2 S1. Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 83:11:6, and pure water was added and stirred to dissolve, preparing a ternary solution with a total metal ion concentration of 1.8 mol / L. A 2 mol / L aqueous solution of sodium bicarbonate was prepared as a precipitating agent solution. A complexing agent solution was prepared with a concentration ratio of 3 between aqueous ammonia and sodium bicarbonate. A citric acid solution was prepared as a treatment solution, and the concentration ratio of the citric acid solution to sodium bicarbonate was 0.015.

[0052] S2. Nitrogen gas was injected using an air pump, and the complexing agent solution was added to pure water under a nitrogen atmosphere. The primer solution was controlled to pH 11 with a precipitating agent solution, with an ammonia concentration of 8 g / L, a temperature of 60°C, and a stirring speed of 600 rpm.

[0053] S3. Under a nitrogen atmosphere, the prepared ternary solution and treatment solution were injected into the primer solution and reacted. The stirring speed of the reaction process was adjusted to 900 rpm, the temperature to 50°C, and the pH to 7.8. After feeding for 1 hour, the air pump was closed, the reaction solution was allowed to stand for 2 hours, and then the supernatant was removed. The pump was opened again, and the ternary solution, precipitant solution, and complexing agent solution were continuously injected by the pump and reacted, allowed to stand, and the supernatant was removed. This process was repeated 5 times. After the reaction was complete, the mixture was aged for 12 hours, the aged slurry was washed with deionized water, allowed to stand for 1 hour, the supernatant was removed, and this was repeated 8 times to remove impurity ions. The mixture was dried in a vacuum chamber at 80°C for 15 hours, and the resulting powder was passed through a 200-mesh sieve to remove iron, after which a spiky nodular precursor was obtained.

[0054] Method for manufacturing positive electrode material: 3 g of the obtained spiky nodular precursor and 1.526 g of lithium hydroxide (molar ratio of spiky nodular precursor to lithium hydroxide: 1:1.07) were ball-milled at a rotation speed of 1800 r / min for 3 hours and thoroughly mixed. The mixed material was placed in a tubular furnace and heat-treated with oxygen gas at a flow rate of 80 mL / min. The heat treatment involved first raising the temperature from room temperature to 480°C and holding the temperature for 4 hours, then raising the temperature to 750°C and holding the temperature for 12 hours, after which the furnace temperature was lowered to room temperature, with a heating rate of 3°C / min during the heat treatment process. The obtained material was removed and passed through a 200-mesh sieve to obtain the cathode material.

[0055] Example 3 S1. Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 83:11:6, and pure water was added and stirred to dissolve, preparing a ternary solution with a total metal ion concentration of 2.5 mol / L. A 3 mol / L aqueous solution of sodium carbonate was prepared as a precipitating agent solution. A complexing agent solution was prepared with a concentration ratio of 2 for aqueous ammonia and sodium carbonate. A citric acid solution was prepared as a treatment solution, and the concentration ratio of the citric acid solution to sodium carbonate was 0.025.

[0056] S2. Nitrogen gas was injected using an air pump, and the complexing agent solution was added to pure water under a nitrogen atmosphere. The primer solution was then controlled to pH 12 with a precipitating agent solution, with an ammonia concentration of 12 g / L, a temperature of 60°C, and a stirring speed of 550 rpm.

[0057] S3. Under a nitrogen atmosphere, the prepared ternary solution and treatment solution were injected into the primer solution and reacted. The stirring speed of the reaction process was adjusted to 800 rpm, the temperature to 60°C, and the pH to 8.5. After feeding for 1 hour, the air pump was closed, the reaction solution was allowed to stand for 2 hours, and then the supernatant was removed. The pump was opened again, and the ternary solution, precipitant solution, and complexing agent solution were continuously injected by the pump and reacted, allowed to stand, and the supernatant was removed. This process was repeated 5 times. After the reaction was complete, the mixture was aged for 12 hours, the aged slurry was washed with deionized water, allowed to stand for 1 hour, the supernatant was removed, and this was repeated 8 times to remove impurity ions. The mixture was dried in a vacuum chamber at 80°C for 15 hours, and the resulting powder was passed through a 200-mesh sieve to remove iron, after which a spiky nodular precursor was obtained.

[0058] Method for manufacturing positive electrode material: 3 g of the obtained acicular agglomerated precursor and 1.526 g of lithium hydroxide (the molar ratio of the acicular agglomerated precursor to lithium hydroxide is 1:1.07) were subjected to ball milling at a rotation speed of 1800 r / min for 3 hours for thorough mixing, the mixed material was placed in a tubular furnace and heat-treated with oxygen gas, and the flow rate of the oxygen gas was 80 mL / min. The heat treatment was first performed by raising the temperature from room temperature to 480°C and holding the temperature for 4 hours, then raising the temperature to 750°C and holding the temperature for 12 hours, then the temperature of the furnace was lowered to room temperature, and the temperature rise rate in the heat treatment step was 3°C / min. The obtained material was taken out and passed through a 200-mesh sieve to obtain a positive electrode material.

[0059] Comparative Example 1 A commercially available precursor LiNi was used as the starting material 0.83 Co 0.11 Mn 0.06 O2, and the heat treatment step was performed in the same manner as in Example 1. 3 g of the commercially available precursor LiNi 0.83 Co 0.11 Mn 0.06 O2 and 1.526 g of lithium hydroxide (the molar ratio of the precursor to lithium hydroxide is 1:1.07) were subjected to ball milling at a rotation speed of 1800 r / min for 3 hours for thorough mixing, the mixed material was placed in a tubular furnace and heat-treated with oxygen gas, and the flow rate of the oxygen gas was 80 mL / min. The heat treatment was first performed by raising the temperature from room temperature to 480°C and holding the temperature for 4 hours, then raising the temperature to 750°C and holding the temperature for 12 hours, then the temperature of the furnace was lowered to room temperature, and the temperature rise rate was 3°C / min. The obtained material was taken out and passed through a 200-mesh sieve to obtain a comparative positive electrode material.

[0060] Comparative Example 2 The procedure was carried out in the same manner as in Example 1 except for the following points.

[0061] S3. Under a nitrogen atmosphere, the prepared ternary solution and treatment solution were injected into the primer solution and reacted. The stirring speed during the reaction process was adjusted to 800 rpm, the temperature to 60°C, and the pH to 7.5. After feeding for 1 hour, the air pump was closed and the supernatant was removed. The pump was opened again, and the ternary solution, precipitant solution, and complexing agent solution were continuously injected by the pump. This process was repeated 5 times. After the reaction was complete, the mixture was aged for 12 hours. The aged slurry was washed with deionized water, allowed to stand for 1 hour, the supernatant was removed, and this process was repeated 8 times to remove impurity ions. The mixture was dried in a vacuum chamber at 80°C for 15 hours. The resulting powder was passed through a 200-mesh sieve to remove iron, and a spiky nodular precursor was obtained.

[0062] Comparative Example 3 Except as described below, the procedure was carried out in the same manner as in Example 1.

[0063] S3. Under a nitrogen atmosphere, the prepared ternary solution and treatment solution were injected into the primer solution and reacted. The stirring speed of the reaction process was adjusted to 800 rpm, the temperature to 60°C, and the pH to 7.5. After feeding for 1 hour, the air pump was closed and the reaction solution was allowed to stand for 2 hours. The pump was opened again, and the ternary solution, precipitant solution, and complexing agent solution were continuously injected by the pump. This process was repeated 5 times. After the reaction was complete, the mixture was aged for 12 hours. The aged slurry was washed with deionized water, allowed to stand for 1 hour, the supernatant was removed, and this process was repeated 8 times to remove impurity ions. The mixture was dried in a vacuum chamber at 80°C for 15 hours. The resulting powder was passed through a 200-mesh sieve to remove iron, and a spiky nodular precursor was obtained.

[0064] The positive electrode materials prepared in Comparative Examples 1-3 and Examples 1-3 were fabricated into electrode pieces, and a lithium pair was used as the negative electrode to create a CR2025 type coin cell in a glove box. Charging and discharging were performed as follows: The charge / discharge voltage range was set to 3V to 4.3V, and the charge / discharge current to 0.1C (1C = 180mAh / g). For the cycle performance test, the electrodes were activated by cycling three times at a charge / discharge current of 0.1C, and then a cycle test was performed at 1C. Then, constant current charge / discharge cycles were performed five times each at 1C, 2C, 5C, and 10C, varying the current density.

[0065] Table 1. Electrochemical performance test results of examples and comparative examples of the present invention. TIFF0007936846000001.tif66170

[0066] As is clear from Table 1, the lithium-ion battery manufactured from the cathode material provided in Example 1 of the present invention exhibited excellent cycle performance, with an initial discharge ratio capacity higher than 202 mAh / g and an initial Coulomb efficiency higher than 86% at a rate of 18 mA / g, an initial discharge ratio capacity higher than 188 mAh / g and a 100-cycle capacity retention rate higher than 92%, and an initial intermediate voltage higher than 3.75 V at a rate of 180 mA / g.

[0067] Lithium-ion batteries manufactured using the cathode materials obtained in Comparative Examples 1-3 showed a decrease in initial discharge ratio capacity and Coulomb efficiency at a rate of 18 mA / g compared to Examples 1-3. Furthermore, at a rate of 180 mA / g, the initial discharge capacity, 100-cycle capacity retention rate, and initial intermediate voltage values ​​were also significantly lower than those of Examples 1-3.

[0068] As is clear from Figures 1 and 2, the punctured nodular precursor of the embodiment of the present invention consists of porous particles formed by the aggregation of fine needle-shaped primary particles of uniform size. After heat treatment, secondary particles of uniform particle size are formed, and the product formed after high-temperature firing exhibits excellent cycle characteristics. In Comparative Example 2, the precursor obtained had relatively sparse secondary particles, and the primary particles could not be formed. The product formed after high-temperature firing was prone to cracking during the cycle, leading to a decrease in cycle performance. In Comparative Example 3, the precursor obtained had large voids in the secondary particles, and some of the primary particles did not aggregate. As a result, the product formed after high-temperature firing was prone to cracking during the cycle and had poor cycle characteristics.

[0069] As is clear from Figure 3, the lithium-ion battery manufactured using the cathode material provided in Example 1 had an initial capacity of 203.8 mAh / g at 0.1C, an initial Coulomb efficiency of 86.5%, and a capacity retention rate of 92.8% even after 1C cycling. Comparative Example 1 had an initial discharge ratio capacity of 198.7 mAh / g at 0.1C, an initial Coulomb efficiency of 83.8%, a capacity of 138.0 mAh / g after 100 cycles at 1C, and a capacity retention rate of 74.1%. As is clear from Figure 4, the lithium-ion batteries using the cathode materials of Example 1 and Example 2 are significantly superior to Comparative Example 1 in terms of cycle characteristics at 1C. Furthermore, the present invention also measured the C-rate performance of lithium-ion batteries manufactured using the cathode materials provided in Example 1 and Comparative Example 1 (both from the same lot) at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 10C. As shown in Figure 5, the lithium-ion battery manufactured using the cathode material provided in Example 1 had capacities of 204.4 mAh / g, 200.7 mAh / g, 192.3 mAh / g, 186.8 mAh / g, 180.9 mAh / g, 168.6 mAh / g, and 157.9 mAh / g at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 10C, respectively, demonstrating excellent cycle performance and C-rate performance. On the other hand, the lithium-ion battery manufactured using the cathode material provided in Comparative Example 1 could only achieve a capacity of 54.4 mAh / g at a 10C rate, indicating that both the cycle performance and rate performance of the commercially available precursor were insufficient. Furthermore, the lithium-ion batteries manufactured using the cathode materials of Examples 2 and 3 of the present invention showed significantly superior cycle characteristics and rate characteristics compared to Comparative Example 1. In Figure 3 of the present invention, the horizontal axis represents specific capacity and the vertical axis represents voltage, while in Figures 4 and 5, the horizontal axis represents the number of cycles and the vertical axis represents the discharge ratio capacity.

[0070] Finally, the above-described embodiments are merely illustrative of embodiments of the present invention and do not limit the invention. Although the above-described embodiments have been described in detail with reference to them, those skilled in the art should understand that the embodiments described above can be modified or some features can be equivalently substituted, and such modifications or substitutions will not depart the essence of the corresponding embodiments from the gist and scope of the present invention.

Claims

1. A method for producing a spiky nodular precursor: The aforementioned punctured nodule-shaped precursor is a porous particle formed by the aggregation of fine needle-shaped primary particles. The aforementioned punctate nodular precursor is prepared from a mixture comprising a ternary solution, a precipitant solution, a complexing agent solution, and a treatment solution; The ternary solution is a mixed solution containing nickel salt, cobalt salt, and manganese salt, and the treatment solution is a citric acid solution. The aforementioned manufacturing method is S1. Prepare the ternary solution, precipitating agent solution, complexing agent solution, and treatment solution separately; S2. Under a protective atmosphere of nitrogen, the complexing agent solution and the precipitating agent solution are mixed to prepare a primer solution; S3. The ternary solution, the treatment solution, and the primer solution are mixed, the first reaction is performed, the mixture is allowed to stand, the supernatant is removed, and the first product is prepared; S4. The first product is mixed with the ternary solution, the precipitating agent solution, and the complexing agent solution, the second reaction is carried out, the mixture is allowed to stand, and the supernatant is removed; S5. Repeat step S4 at least once to mature, wash, dry, sieve, and remove iron to produce a nodular precursor of spiky material; Including the process, The temperatures of the first reaction and the second reaction are independently 30 to 60°C; The duration of the first reaction and the second reaction are independently 0.5 to 5 hours; The first reaction and the second reaction have a pH of 7.5 to 8.5, independently of each other. A method for producing a spiky, nodular precursor characterized by the above.

2. The nickel salt, cobalt salt, and manganese salt are independently one or more selected from sulfates, nitrates, and carbonates; and / or The manufacturing method according to claim 1, characterized in that the precipitating agent solution is a carbonate solution.

3. The manufacturing method according to claim 2, characterized in that the carbonate solution is one or more selected from sodium carbonate solution, sodium bicarbonate solution, potassium carbonate solution, potassium bicarbonate solution, and rubidium carbonate solution.

4. The manufacturing method according to claim 3, characterized in that the concentration of the sodium carbonate solution is 0.2 to 4.5 mol / L.

5. The concentration of metal ions in the ternary solution is 0.6 to 2.5 mol / L; The aforementioned precipitating solution is a solution containing carbonate ions; The complexing agent solution is aqueous ammonia; and / or The manufacturing method according to claim 1, characterized in that the concentration of the citric acid solution is 0.025 to 0.1 mol / L.

6. The manufacturing method according to claim 5, characterized in that the carbonate ion concentration in the precipitant solution is 0.8 to 3.4 mol / L.

7. The manufacturing method according to claim 5, characterized in that the concentration of the ammonia water is 4 to 7 mol / L.

8. The primer solution has a pH of 11 to 12; and / or The manufacturing method according to claim 1, characterized in that the ammonia concentration in the primer solution is 2 to 20 g / L.

9. The manufacturing method according to claim 1, characterized in that the maturation time is 5 to 20 hours.

Citation Information

Patent Citations

  • Latticed porous precursor material and preparation method thereof and positive electrode material

    CN111153447A

  • Nickel cobalt complex hydroxide particles and method for producing the same, positive electrode active material for non-aqueous electrolyte secondary battery and method for producing the same, and non-aqueous electrolyte secondary battery

    JP2016210674A

  • Positive electrode active material for secondary battery and secondary battery containing the same

    JP2018538663A

  • Positive electrode active material, its manufacturing method, and lithium secondary battery including the same

    JP2021536662A

  • Cathode active material for lithium secondary battery, cathode including same, and lithium secondary battery including same

    US20200343552A1